Scalable production of double emulsion drops with thin shells. Issue 13 (8th June 2018) - Vian, A.; Reuse, B.; Amstad, E.
Abstract : The microfluidic aspiration device reduces the shell thickness of double emulsions down to 240 nm at a high throughput. Abstract : Double emulsions are often used as containers to perform high throughput screening assays and as templates for capsules. These applications require double emulsions to be mechanically stable such that they do not coalesce during processing and storage. A possibility to increase their stability is to reduce the thickness of their shells to sufficiently low values that lubrication effects hinder coalescence. However, the controlled fabrication of double emulsions with such thin shells is difficult. Here, we introduce a new microfluidic device, the aspiration device, that reduces the shell thickness of double emulsions down to 240 nm at a high throughput; thereby, the shell volume is reduced by up to 95%. The shell thickness of the resulting double emulsions depends on the pressure profile in the device and hence on the fluid flow rates in the channels and is independent of the shell thickness of the injected double emulsions. Therefore, this device enables converting double emulsions with polydisperse shell thicknesses into double emulsions with well-defined, uniform thin shells.